Advances in hearing rehabilitation - Lloyd, Simon Kingsley Wickham; Donnelly, Neil Patrick 1972- (Basel : Karger, 2018)
The development of new technology in hearing aid devices as well as imaging techniques has improved the possibilities of meeting the patient's individual needs. This book, in which experts from around the world have contributed, comprehensively covers advances in all aspects of hearing implantation otology. Chapters review the evidence behind the current applications of the wide range of hearing implants available for different types of hearing loss. Further articles discuss the extended applications of implantation otology and let us have a glimpse into the future of hearing rehabilitation. New imaging techniques for the middle and inner ear are explored as well as innovations to improve Eustachian tube function. The publication is essential reading to otolaryngologists, audiologists and hearing rehabilitation professionals. It provides comprehensive coverage of state of the art hearing rehabilitation across the spectrum of hearing loss: as such it is a perfect tool for those who wish to develop their knowledge within the field.
Keywords: AUDÍFONOS; IMPLANTE COCLEAR; PERSONAS CON DAÑO AUDITIVO -- REHABILITACIÓN; SORDOS -- REHABILITACIÓN